ON THE PROBLEM OF THE STADY OF PERSONALITY TRAITS OF THE HEAD OF THE INSTITUTION - Red’ko, Serhii (Continuing Professional Education: Theory and Practice, 2019)
Successful operation of an educational institution is largely dependent on the professionalism, personality traits and business manager. Modern management practices in the education sector confirms the need to prepare a modern head of the institution – professional educational sector, which has a new way of thinking and willing to constant selfimprovement and self-development, learning innovative management techniques and implement them in daily management activities . The aim of the paper is to further study the personal qualities of the head of the educational institution and the analysis of the psychological “portrait”. The study of personality traits of the head of an educational institution attended by 32 respondents – managers of secondary schools. The aim of our study was to make a psychological “portrait” of the modern manager educational organization that will identify its individual psychological characteristics in the exercise of governmental activity. To determine the personality of the leaders of schools and pre-school programs for performance management activities used test “Cattell 16 Factor Questionnaire”. The results of this technique can determine the originality of the main substructures of temperament and character personality. Awareness of psychological “portraits” of the modern manager educational organization suggests the need to develop new criteria for the selection of school leaders, detailed staffing and further their education .